Investigation in Techniques for Using Sewage Sludge as an Energy Feedstock: Poland’s Experience - Vambol, Viola; Kowalczyk-Juśko, Alina; Jóźwiakowski, Krzysztof; Mazur, Andrzej; Vambol, Sergij; Khan, Nadeem A. (Ecological Questions, 2022)
The sludge generated from wastewater treatment facilities contains high nutrients and is characterized by high heating values. Thus, the sludge enriched with organic matter and nutrients is a potential candidate for its application as fertilizers and an alternate energy feedstock. Nowadays, energy independence contributes to the economic stability of the country, and therefore the search for alternate energy sources is an acute issue. This paper presents a case study on using sewage sludge as an energy feedstock in Poland. The physicochemical characteristics of the sewage sludge are presented. The fuel properties of sewage sludge generated from different waste water treatment plant (WWTP) are summarized. The calorific value of sewage sludge generated in Poland is insufficient for effective use as an energy raw material, therefore, energy potential of mixture of sludge with other waste have been studied. The general trend of sewage sludge formation and the quantitative forecast for the future showed that in 2020, compared to 2012, sludge accumulation increased by 6.9%, but compared to 2019 – decreased by 3%. From 2012 to 2020 the average, sewage sludge accumulation increased annually by 0.8%. This demonstrates the heterogeneity of waste streams for the production of alternative fuels and a modest increase in sewage sludge production in the coming years. This made it possible to prepare several options for the further development of research in the field of developing technologies for obtaining alternative energy. Also this study will help the prospective researchers understand sewage sludge generation and its use as energy feedstock.